Electrocatalysis by Design: Low Dissolution Counter Electrode and Highly Efficient Nanostructured Electrocatalysts - Hasan, Menna (AUC Knowledge Fountain, 2022)
Water Electrolysis is one of the most promising techniques to generate H2 gas, which is an alternative clean source of energy. Hydrogen provides almost three times the energy provided by gasoline, helping to solve the global warming problem caused by the currently used fossil fuels. As any electrochemical reaction is composed of two half reactions, a setup of working and counter electrodes is used to study the catalytic activity towards the targeted reaction, where each electrode carries one of the two-half reactions. In this dissertation, the stability of a number of the commonly used counter electrodes was examined to identify a stable counter electrode to avoid the deceptive enhancement caused by the dissolution and redeposition of the counter electrode on the working electrode during operation. Commercial titanium mesh has been introduced as an alternative emerging low‑dissolution counter electrode, which was proven to be very stable and convenient to study the HER in acidic media. The second part of the dissertation focused on the working electrode, where various nanostructures were explored as catalysts for both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). First, boron carbon nitride (BCN) nanosheets were studied as an electrocatalyst for HER. BCN comprises the unique physicochemical properties of both graphene and 2D hexagonal boron nitride, including the electrical conductivity, mechanical, and chemical stability. Besides, the heteropolar bonding between N and B can improve its electroactivity. An innovative technique was introduced to fabricate 2D BCN hetero-structure nanosheets with various Cu:BCN weight ratios. The fabricated composites showed unique electrocatalytic properties for HER. Specifically, the overpotential of the 0.125 Cu-BCN composite at a current density of -10 mA/cm2 vs RHE is 50% lower than that of pristine BCN. Moreover, C76 was investigated as a 0D catalyst, which showed tremendous enhancement in the catalytic HER activity due to the synergistic effect between C76 and nickel foam substrate. The C76/Ni showed almost the same activity as the benchmark Pt/C catalyst. Finally, NiCoMnFe-phosphide nanosheets deposited on commercial Ti mesh were investigated as a ternary electrocatalyst for both HER and OER. The electrochemical measurements showed the NiCoMnFe-P composite to have the lowest overpotential towards HER (-200 mV) at -10 mAcm-2, lowering the overpotential needed to drive the reaction by almost 40% for HER compared to that of blank Ti mesh. For overall water splitting, a cell voltage of 1.71 V was recorded at a current density of 10 mAcm-2.